English Participial Clauses Aand The Strategies Applied In Their Indonesian Translations - Menik Winiharti (Bina Nusantara University, 2007)
This study analyses the English participial clauses and how they are translated into Indonesian as appearing in Sidney Sheldon’s novel Morning, Noon and Night (1995) which is translated by Hendarto Setiadi as Pagi, Siang dan Malam (1996). This study tries to find out the distribution of the types and the syntactic functions of the participial clauses appearing in the novel and answer the question of what the strategies applied in the translations are. To reach these objectives, this study employs an exploratory-interpretive design since the data are collected nonexperimentally, the type of data collected is qualitative, and the type of analysis is interpretive.